BRAINWASHING ANALYSIS OF RADICAL EXTREMISM ADHERENTS IN ISLAM THROUGH A PSYCHOLOGICAL APPROACH - Santoso, Erik; Priambodo, Dhito; Hosali, Aulia Siti Kholisah; Suprianti, Silvia; Noor, Aditia Muhammad (Academic Solution Publisher, 2024)
This article aims to analyze and identify how a radicalist uses brainwashing to spread his radicalism to others. The data collection technique that we do is literature study. The analysis uses a qualitative descriptive method with library studies and concluding. The results of this study indicate that a radicalist has specific criteria for potential victims who are easily influenced by the notion of extremist radicalism. These potential victims tend to emerge from among people who want changes to the existing social order. They will attack the victim's subconscious so that he will follow the words of the doctrine to carry out acts of terror with the brainwashing method.